Study on the therapeutic material basis and effect of Acanthopanax senticosus (Rupr. et Maxim.) Harms leaves in the treatment of ischemic stroke by PK-PD analysis based on online microdialysis–LC-MS/MS method. Issue 3 (20th February 2020) - Wang, Yu; Liu, Shu; Wang, Rongjin; Shi, Liqiang; Liu, Zhiqiang; Liu, Zhongying
Abstract : The therapeutic material basis and effect of ASL in the treatment of ischemic stroke were studied by PK-PD analysis. Abstract : Leaves of Acanthopanax senticosus (Rupr. et Maxim.) Harms (ASL) have revealed significant biological activity in the treatment of ischemic stroke diseases. However, there was no in-depth study of the therapeutic material basis and effect of ASL from the pharmacokinetics–pharmacodynamics (PK-PD) analysis level. In this study, a method based on microdialysis coupled with ultra-performance liquid chromatography combined with triple quadruple mass spectrometry (MD-UPLC-QQQ-MS) was established to simultaneously and continuously collect and quantify the active compounds and endogenous neuroactive substances related to therapeutic effect in plasma and hippocampus of fully awake ischemic stroke rats. The acquired data were analyzed by the PK-PD analysis method. It was found that hyperoside, quercitrin, quercetin, and caffeic acid could pass through the blood–brain barrier, and quercetin needed a longer intake time than quercitrin and hyperoside, but the passage rate was higher. The exposure of the four compounds in the hippocampus affected the contents of seven neuroactive substances in different ways and was depicted graphically (concentration–time effect). In addition, the study found that the brain index and brain water content of ischemic stroke rats were significantly reduced after the oral administration of ASL. ASL observably regulated the content or activity of six important biochemical indexes in rats. On the one hand, this study verified that ASL could regulate ischemic stroke in many aspects. On the other hand, a visualized method to express the relationship between pharmacokinetics and pharmacodynamics in the hippocampus of cerebral ischemic areas was established. This research gives a hand to the study on the therapeutic material basis and effect of traditional Chinese medicine mechanism.